Comparison of body fat using various bioelectrical impedance analyzers in university students - Petr Kutáč; Miroslav Kopecký (Palacký University Olomouc, 2015)
Background: At present, the portfolio of devices using the bioelectrical impedance (BIA) method is continuously expanding as a result of the wide use of this method in the field as measurements by this method are fast and staff training is simple and reasonably priced. Nonetheless, the problem is that despite using the same method, bioimpedance analyzers can differ in many parameters. They use different electric current frequencies, a different number of electrodes and the electric current may be conducted through different parts of the body.Objective: The main objective of the study is to compare and evaluate the differences of values of the analysis of the body fat of university students measured by BIA analyzers that differ in the applied electric current frequency, number of electrodes and flow of the electric current through the individual body parts.Methods: The research included 125 participants (70 male and 55 female). The measurements were taken by the following analyzers: Tanita 418 MA, InBody 720, InBody R20 and Omron BF 300.Results: The differences in the mean values of the body fat representation between the used analyzers in men ranged from 0.1 to 3.4% and from 0.0 to 2.4 kg, in women from 0.5 to 6.5% and from 0.4 to 3.8 kg in relation to the used analyzer.Conclusions: In men with regular physical activity, the values measured by InBody R20 were statistically and practically different. The analyzer measured higher values that other analyzers. In women, there were statistically and practically significant differences in the values measured by Omron BF 300. This analyzer measured lower values than other analyzers.